“APLIKASI ANDROID (SCAN EVENTKU) UNTUK MENDUKUNG PEMBELAJARAN REGISTRASI EVENT” - Azhari, Ozmar; Christianto, Kevin; Bernanda, Devi Yurisca; Andry, Johanes Fernandes (Universitas Bunda Mulia, 2019)
Technological developments have changed human behavior, including the behavior of junior high school students. Now generally junior high school students are already very active in using mobile phones, including using this Android Behavior, making the idea of students of the University of Bunda Mulia, major Information System to development interactive learning media based on Android, which are considered not boring, and more effective for improving student quality. In designing the media a set of Android applications was created called Scan Evenku to Support Learning Event Registration. Learning media which are the work of students are software that can be installed on mobile phones, like interesting games. The application has been tested by RPTRA Darma Suci Penjaringan, North Jakarta. From the results that have been tested, the application was warmly welcomed and the students seemed enthusiastic to use it.Technological developments have changed human behavior, including the behavior of junior high school students. Now generally junior high school students are already very active in using mobile phones, including using this Android Behavior, making the idea of students of the University of Bunda Mulia, major Information System to development interactive learning media based on Android, which are considered not boring, and more effective for improving student quality. In designing the media a set of Android applications was created called Scan Evenku to Support Learning Event Registration. Learning media which are the work of students are software that can be installed on mobile phones, like interesting games. The application has been tested by RPTRA Darma Suci Penjaringan, North Jakarta. From the results that have been tested, the application was warmly welcomed and the students seemed enthusiastic to use it.